Strategi penjualan Sumatera Utara Inbound Tour di PT. Narasindo Medan - Krisna Gerda Simanjuntak; Emelia Fransiska Ginting (Jurnal Ilmiah Akomodasi Agung, 2018)
This research entitled: Sales Strategy of North Sumatera Inbound Tour in PT. Narasindo Medan. This research aims to determine the strategies, procedures and problems associated in sales of North Sumatera Inbound Tour in PT. Narasindo Tour & Travel Medan. This research uses qualitative descriptive method, which becomes subjects in this research is all staff of PT. Narasindo Medan and the samples are Inbound Tour staff consist of 7 people. The results of this research indicate that PT. Narasindo Medan has a good sales strategy in terms of sales of North Sumatera Inbound Tour by creating appropriate products/services, according to market or demand, making tourism components attractive and channeled along with other public travel bureaus in tourism. In terms of Inbound Tour sales procedure is sufficient but still has drawbacks: not actively doing promotions including in various media available which is very helpful. The problems that PT. Narasindo Medan struggled in terms of selling the inbound tour of North Sumatera are a very tight competition because of the travel agent increase more in this time and also online travel agent which more practice and easier for customers.